2015
DOI: 10.1002/pi.4933
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional crystalline supramolecular nanostructures from self‐assembly of rod–coil molecules incorporating lateral carboxyl group in the middle of the rod segment

Abstract: We report the synthesis and self-assembling behaviour of coil-rod-coil molecules 1a-1c and 2a-2c, which incorporate lateral carboxyl or ester groups in the middle of the rod segment. The self-assembling behaviour of these molecules was investigated in the bulk using differential scanning calorimetry, polarised optical microscopy and small-angle X-ray scattering. Our results reveal that hydrogen bonds strongly influence the self-assembling behaviour of rod-like building blocks. Molecules 1a-1c, which incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Amphiphilic rod–coil molecules consisting of rigid rod segments and flexible hydrophilic poly­(ethylene oxide) (PEO) coil chains are also known to form various supramolecular aggregates with well-defined shapes and sizes, such as spherical micelles, cylindrical micelles, ribbons, vesicles, tubules, helices, and toroids in selected solutions. These self-assembling nanostructures, constructed through noncovalent forces, including hydrophobic and hydrophilic effects, electrostatic interactions, hydrogen bonding, and van der Waals interactions, could be widely utilized as biomimetic or bioinspired materials in aqueous solutions. We reported that supramolecular nanostructures can be accurately controlled by incorporating lateral alkyl groups at the surface of the rod and coil segments or at the center of the rod building block. This can significantly influence microphase separation of the rod–coil molecules and lead to the creation of hexagonal perforated layer, oblique columnar, and 3-D body-centered tetragonal nanostructures in bulk, and the formation of micelles, vesicles, and helical nanofibers in aqueous solutions, by tuning the self-assembling driving force of the rod building block. These results indicate that the lateral chains in the rod domain can suppress the intermolecular π–π stacking interaction that leads to the relatively loose packing of the rod segments of different nanoassemblies.…”
Section: Introductionmentioning
confidence: 99%
“…Amphiphilic rod–coil molecules consisting of rigid rod segments and flexible hydrophilic poly­(ethylene oxide) (PEO) coil chains are also known to form various supramolecular aggregates with well-defined shapes and sizes, such as spherical micelles, cylindrical micelles, ribbons, vesicles, tubules, helices, and toroids in selected solutions. These self-assembling nanostructures, constructed through noncovalent forces, including hydrophobic and hydrophilic effects, electrostatic interactions, hydrogen bonding, and van der Waals interactions, could be widely utilized as biomimetic or bioinspired materials in aqueous solutions. We reported that supramolecular nanostructures can be accurately controlled by incorporating lateral alkyl groups at the surface of the rod and coil segments or at the center of the rod building block. This can significantly influence microphase separation of the rod–coil molecules and lead to the creation of hexagonal perforated layer, oblique columnar, and 3-D body-centered tetragonal nanostructures in bulk, and the formation of micelles, vesicles, and helical nanofibers in aqueous solutions, by tuning the self-assembling driving force of the rod building block. These results indicate that the lateral chains in the rod domain can suppress the intermolecular π–π stacking interaction that leads to the relatively loose packing of the rod segments of different nanoassemblies.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks can be assigned to the (100), (010), (210), and (300) reflections of a two-dimensional oblique columnar structure with a characteristic angle γ = 64° (Figure a) and lattice constants a = 5.13 nm and b = 2.97 nm (Table S2). In addition, three peaks of 1a corresponding to the equidistant q-spacings in the small-angle region can be assigned to the (001), (002), and (003) reflections, indicating a lamellar structure in the crystalline phase. The measured layer spacing of 4.7 nm is close to the estimated molecular length (the estimated lengths of the rod segment and coil chain are ∼3.1 and ∼4.1 nm from the Corey–Pauling–Koltun (CPK) molecular model, respectively). This suggests that a typical monomolecular layer structure was formed in which the rod segments are fully interdigitated with each other (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 3 and 4 were prepared according to the references described elsewhere (see the Supporting Information). [14] Characterization:F lash column chromatography was performed using silica gel (200-300 mesh). 1 HNMR(300 MHz) was recorded in CDCl 3 on Bruker AM-300 instruments.…”
Section: Methodsmentioning
confidence: 99%